At home with the boss: Migrant live‐in caregivers, social reproduction and constrained agency in the UK, Canada, Austria and Switzerland. Issue 3 (16th April 2018) - Schwiter, Karin; Strauss, Kendra; England, Kim
Abstract : In many countries of the global North, families increasingly rely on live‐in caregivers to look after their children and elderly. Although much care work remains unpaid and informal, several states have set up a variety of migration and labour regimes to guarantee a steady supply of workers to provide paid live‐in care in the home. This paper contributes to a broadening of the focus of labour geography beyond "productive" labour by factoring in the theoretical perspective of social reproduction into the debates on constrained agency. Our aim is to identify the mechanisms that make these regimes function for employers and employees, and their consequences for the social reproduction of the workers. To do so we compare live‐in care schemes in the UK, Canada, Austria and Switzerland and examine the ways in which live‐in care is differentially institutionalised. Our policy analysis in these four countries shows that the constrained agency of the workers does not solely stem from their status as migrants, but is produced by the nexus of specific migration, care and gendered labour regimes. Furthermore, we argue that we need to extend our perspective beyond the immediate work context to see how live‐in care regimes not only infringe, but also enable, the social reproduction of the workers – a fact that has often been neglected by existing research.